Assessing mammal responses to perturbations in temperate aridlands of Argentina - Tabeni, Maria Solana (2003)
Loss of species richness and reduced abundance have been the main responses to perturbations of small- and medium-sized mammals in arid and semi-arid areas. Nonetheless, some mammal species whose habitat requirements are met in disturbed patches may benefit from structural changes in the environment brought about by perturbations. In desert areas of Argentina different mammal responses are attributable to both a lower complexity of disturbed patches and a decrease in sheltered places. Therefore, species associated with high plant cover either decrease in number or become locally extinct at sites affected by fire or grazing, whereas species using open areas are favored by these events. The negative effects historically assigned to different disturbances may be mitigated by adopting a hierarchical approach that considers patch diversity in different successional stages as well as the multiple opportunities of patch occupation by mammal species.